The Effect of Open-Ended Worksheets in Interactive Demonstration Learning on Students’ Conceptual Understanding of Harmonic Motion and Scientific Reasoning - Arrosyid, Abdur Rohman Wahid; Kusairi, Sentot; Wisodo, Hari (Universitas Negeri Malang, 2024)
This research explores the influence of using open-ended worksheets in interactive demonstration learning on students' understanding of harmonic motion and scientific reasoning. It is a quasi-experimental study with a pretest-posttest control group design. Data were obtained from conceptual understanding and scientific reasoning tests and analyzed using parametric and non-parametric tests. The results show that open-ended worksheets enhance students' concept comprehension and scientific reasoning. There was a significant difference in conceptual understanding between the two classes. However, there was no difference in scientific reasoning. These findings hold valuable implications for improving learning with open-ended worksheets and interactive demonstration models.